2022
DOI: 10.1155/2022/1088371
|View full text |Cite|
|
Sign up to set email alerts
|

Tooth Loss and the Incidence of Ischemic Stroke and Transient Ischemic Attack: A Systematic Review and Meta-Analysis

Abstract: Generally, as the population is aging, ischemic stroke is imposing rising social and economic burdens. On that basis, the early intervention and prevention of ischemic stroke turns out to be a major public health issue. Extensive studies have reached mixed conclusions regarding the correlation between tooth loss and ischemic stroke, as well as transient ischemic attack (TIA). In this paper, a systematic review and meta-analysis is presented where we have aimed to examine whether tooth loss is correlated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Periodontitis reportedly increased the risk of cardiovascular and several vascular diseases [ 19 , 20 ]. Tooth loss, an indicator of poor oral health, was positively correlated with a higher risk of hypertension [ 21 ] and stroke [ 22 ]. Studies showed that the bacteremia can be caused by periodontitis and poor oral hygiene, [ 23 ] and inflammation induced by oral infection produced pro-inflammatory cytokines [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis reportedly increased the risk of cardiovascular and several vascular diseases [ 19 , 20 ]. Tooth loss, an indicator of poor oral health, was positively correlated with a higher risk of hypertension [ 21 ] and stroke [ 22 ]. Studies showed that the bacteremia can be caused by periodontitis and poor oral hygiene, [ 23 ] and inflammation induced by oral infection produced pro-inflammatory cytokines [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis reportedly increases the risk of cardiovascular and several vascular diseases [ 21 , 22 ]. Tooth loss, an indicator of poor oral health, is positively correlated with an increased risk of hypertension [ 23 ], stroke [ 24 ], and increased levels of thrombotic variables [ 25 ] which are associated with thrombus formation. According to a previous cross-sectional study, a higher prevalence of periodontitis was detected in patients with VTE than in healthy participants, suggesting a potential association between periodontitis and VTE [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al found that patients who had stroke had poorer oral health than the healthy population, with more dental caries but fewer remaining teeth and worse periodontal status [ 13 ]. Periodontal disease is a risk factor for stroke, with the direct mechanism remaining unclear [ 14 ]. Health literacy involves obtaining, understanding, and using health information to make appropriate health decisions and follow treatment instructions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%